Gastroesophageal reflux after peroral endoscopic myotomy: a multicenter case–control study - Kumbhari, Vivek; Familiari, Pietro; Bjerregaard, Niels Christian; Pioche, Mathieu; Jones, Edward; Ko, Weon Jin; Hayee, Bu; Cali, Anna; Ngamruengphong, Saowanee; Mion, Francois; Hernaez, Ruben; Roman, Sabine; Tieu, Alan H.; El Zein, Mohamad; Ajayi, Tokunbo; Haji, Amyn; Cho, Joo Young; Hazey, Jeffrey; Perry, Kyle A.; Ponchon, Thierry; Kunda, Rastislav; Costamagna, Guido; Khashab, Mouen A. (Endoscopy, 2017)
Background and study aims The variables associated with gastroesophageal reflux (GER) after peroral endoscopic myotomy (POEM) are largely unknown. This study aimed to: 1) identify the prevalence of reflux esophagitis and asymptomatic GER in patients who underwent POEM, and 2) evaluate patient and intraprocedural variables associated with post-POEM GER.Patients and methods All patients who underwent POEM and subsequent objective testing for GER (pH study with or without upper gastrointestinal [GI] endoscopy) at seven tertiary academic centers (one Asian, two US, four European) were included. Patients were divided into two groups: 1) DeMeester score ≥ 14.72 (cases) and 2) DeMeester score of < 14.72 (controls). Asymptomatic GER was defined as a patient with a DeMeester score ≥ 14.72 who was not consuming proton pump inhibitor (PPI).Results A total of 282 patients (female 48.2 %, Caucasian 84.8 %; mean body mass index 24.1 kg/m2) were included. Clinical success was achieved in 94.3 % of patients. GER evaluation was completed after a median follow-up of 12 months (interquartile range 10 – 24 months). A DeMeester score of ≥ 14.72 was seen in 57.8 % of patients. Multivariable analysis revealed female sex to be the only independent association (odds ratio 1.69, 95 % confidence interval 1.04 – 2.74) with post-POEM GER. No intraprocedural variables were associated with GER. Upper GI endoscopy was available in 233 patients, 54 (23.2 %) of whom were noted to have reflux esophagitis (majority Los Angeles Grade A or B). GER was asymptomatic in 60.1 %.Conclusion Post-POEM GER was seen in the majority of patients. No intraprocedural variables were identified to allow for potential alteration in procedural technique.